Palladium-catalyzed cascade cyclization of ynamides to azabicycles. - Greenaway, R; Campbell, C; Holton, O; Russell, C; Anderson, E (2011)
Cascade reactions: A modular assembly of azabicycles by using a cascade cyclization/Suzuki coupling/6π-electrocyclization of bromoenynamides is reported. The reaction offers a wide substituent scope on the bicyclic aminodiene products, which can be selectively oxidized as a general approach to aromatic azabicycles.